توجه المصارف نحو التمويل المستدام كآلية لدعم الاقتصاد الأخضر دراسة تجارب مختلفة - جلال،سراي; حورية،بن عودة; سارة،نايلي (university of eloued جامعة الوادي, 2024)
جاءت هذه الدراسة والتي تبين مدى توجه المصارف نحو التمويل المستدام كآلية لدعم الاقتصاد الأخضر، حيث تهدف إلى معرفة العلاقة بين كل من المصارف والتمويل المستدام والاقتصاد الأخضر، من خلال دراسة تجارب بعض البنوك والمصارف لدول من العالم كبنك أبوظبي الأول للإمارات العربية المتحدة، وبنك Triodos لمملكة هولندا وبنك الرياض للمملكة العربية السعودية، واتبعنا خلال دراستنا هذه المنهج الوصفي التحليلي، حيث توصلنا من خلالها إلى أن هاته البنوك تعمل جاهدة من أجل التوجه نحو التمويل المستدام الذي يراعي الأبعاد البيئية والاجتماعية والحوكمة وتحقيق التنمية المستدامة كما توصلنا إلى أن هنالك علاقة تكاملية بين المصارف والتمويل المستدام والاقتصاد الأخضر، من خلال توجيه الموارد المالية نحو المشاريع الصديقة للبيئة، وتساهم المصارف في دعم الاقتصاد الأخضر أكثر استدامة وشمولية. This study shows the extent to which banks are moving towards sustainable financing as a mechanism to support the green economy, as it aims to know the relationship between banks, sustainable financing and the green economy, by studying the experiences of some banks and banks in countries around the world, such as the First Abu Dhabi Bank of the United Arab Emirates, and the United Arab Emirates Bank. Triodos of the Kingdom of the Netherlands Bank Riyadh for the Kingdom of Saudi Arabia, and during our study we followed this descriptive and analytical approach, through which we concluded that these banks are working hard to move towards sustainable financing that takes into account the environmental, social and governance dimensions and achieving sustainable development. We also concluded that there is a complementary relationship between banks and sustainable financing. green economy, By directing financial resources towardsenvironmentally friendly projects, banks contribute to supporting a more sustainable and inclusive green economy.
مذكرة ماستر اقتصاد
Keywords: المصارف، التمويل المستدام، الاقتصاد الأخضر، الاستدامة المصرفية. banks; sustainable finance; green economy; banking sustainability.